Misguided approach to dengue vaccine risk - Wilder-Smith, Annelies; Hombach, Joachim; Cravioto, Alejandro (Science, 2019)
In the In Depth News story “Controversy over dengue vaccine risk” (6 September, p. [961][1]), J. Cohen describes the anxiety of parents whose children were vaccinated with Dengvaxia after warnings that the vaccine could lead to severe dengue in rare cases in children who were seronegative (i.e., had never had a prior dengue infection) at the time of first vaccination. Vaccinated children who were seropositive at the time of vaccination experienced substantial protection, whereas children who were seronegative when vaccinated were found to be at higher risk of severe dengue than seronegative unvaccinated children ([ 1 ][2]). It is natural for parents to fear that their children were seronegative at the time of their vaccination and hence at increased risk, but these fears should not be unnecessarily exacerbated. Cohen quotes Leonila and Antonio Dans, who call for testing of all vaccinated children to retrospectively determine their baseline serostatus before the administration of Dengvaxia. This approach is misplaced. - - In a seroprevalence setting in the Philippines estimated to be as high as 85% ([ 2 ][3]), the vast majority of vaccinated children are seropositive and will benefit from the vaccine. As for many other vaccines, protective efficacy is not complete but reported to be 76% in seropositive vaccinated persons ([ 1 ][2]). Therefore, one would expect breakthrough disease, including severe dengue, in about 24% of seropositive vaccinated persons as a result of exposure to natural infection given the current dengue outbreak in the country ([ 1 ][2]). The clinical spectrum of severe dengue in seronegative vaccinated children is the same as in seropositive vaccinated or seropositive unvaccinated children ([ 1 ][2], [ 4 ][4]). Thus, clinical management of severe dengue is the same, irrespective of baseline serostatus at the time of administration of Dengvaxia. Testing vaccinated children would not change clinical management. - - Moreover, as Cohen points out, commercially available dengue immunoglobulin G enzyme-linked immunosorbent antibody (ELISA) testing will not be able to differentiate the effect of vaccination from the effect of natural dengue infection, and therefore it cannot identify those children who were seronegative at baseline. An elaborate assay such as the novel NS1-based ELISA assay ([ 3 ][5]) must be used to retrospectively infer baseline serostatus. However, the ability of the NS1 assay to correctly detect “dengue-exposed” individuals as seropositive is estimated to be 95.3%, which means that the false negative rate (seropositive samples misclassified as seronegative) is 4.7%. The ability of the assay to correctly identify dengue unexposed individuals as seronegative is estimated to be 68.6%, which means that the false seropositive rate (seronegative samples misclassified as seropositive by the assay) is 31.4% ([ 4 ][4]). Therefore, among subjects classified as seropositive by the anti-NS1 assay, a proportion would be actually seronegative and vice versa. This would result in unnecessary anxiety for those tested seronegative although they are actually seropositive and would falsely reassure those tested seropositive who are actually seronegative. Furthermore, given the high annual dengue incidence in the Philippines, many of the originally seronegative children vaccinated in 2016 have meanwhile been exposed to dengue infections and become seropositive. These children would also be misclassified as seropositive. - - The costs and logistics of testing about 800,000 children are immense and totally disproportionate to the benefit. The money would be better spent on improving clinical case management and setting up centers of excellence to ensure better health outcomes of dengue patients, regardless of vaccination status.